(untitled) ("Conference on Universal Science Research 2023", 2024)
A semantic system in English neologism refers to the underlying meaning and structure of newly coined words or terms in the English language. It involves understanding the connections between the new word and its intended meaning, as well as how it fits into the existing semantic framework of the language. This includes analyzing the morphological, syntactic, and semantic properties of the neologism to determine its function and usage within the language.A semantic system in English neologism refers to the way new words are created and how they convey meaning within the language. It involves analyzing the semantic components of new words, including their root meanings, prefixes, suffixes, and any other linguistic elements that contribute to their overall meaning.This annotation provides insight into the process of creating and understanding neologisms in English, highlighting the importance of considering not only the form but also the underlying meaning and structure of these newly coined terms. By examining the semantic system of English neologisms, linguists can gain a deeper understanding of how language evolves and adapts to meet new communication needs.